Strategi Menumbuhkan Minat Masyarakat Pada Asuransi Jiwa Syari'ah - Yulianto, Dedi; Jauhari, Tontowi (BINA' AL-UMMAH, 2019)
This research is aimed to explore  how the AL AMIN Syaria Insurance as a branch of Syariah Life Insurance, innovate effective strategies in marketing insurance service products owned by this institution; fostering interest in people's interest in insurance, especially by building cooperation and collaboration. Data on shari'ah institutional cooperation and efforts to foster community interest are obtained by using a qualitative approach, particularly through interviews. Data collected then analyzed by the balanced scorecard to see the performance of the strategies used.The results of this study indicate that the strategy used was first,establishing collaboration with banks and other financial institutions; second, fast service; and third, simplifying administrative procedures and requirements. Fast service and simplifying administrative procedures and requirements were more strategic approach in growing public interest in using the Lampung branch of the AL AMIN Sharia Life Insurance service.